Psychological Mechanisms of Non-Physical State Repression: A Systematic Review of Collective Protest Research - Syarif, Akhmad Saputra (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Research on state repression of protest has predominantly focused on the use of physical violence, while non-physical forms of repression that operate in subtle and psychological ways have received comparatively less attention. This study aims to examine how psychological mechanisms operate in responses to non-physical state repression of collective action. The study employs a Systematic Literature Review (SLR) approach following PRISMA guidelines, through a literature search in the Scopus and Web of Science databases. From an initial pool of 474 documents, 21 articles that met the inclusion criteria were analyzed in depth. The review identifies four main psychological mechanisms: affective, symbolic, traumatic, and memory-based mechanisms. Affective mechanisms operate through the activation of emotions such as fear, guilt, and respect, which reduce collective efficacy and protest intentions. Symbolic mechanisms function through labeling, moral panic, and discourse control that delegitimize social movements. Traumatic mechanisms indicate the long-term impact of non-physical repression on fear and feelings of helplessness, while memory-based mechanisms operate by managing collective memory to disrupt the historical continuity of resistance. These findings underscore that non-physical repression is widespread, including in democratic contexts, and operates effectively by shaping emotional responses, delegitimizing collective action through discourse and framing, and, in certain contexts, generating enduring traumatic and mnemonic effects that constrain protest participation over time.